Numerical Analysis and Simulation of RM12 turbofan rotor system - Rahmani , Hossein; Moslemi Petrudi, Amin; Cristian Scurtu , Ionut (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
All rotating machines have vibrations and these vibrations have standard limits. The occurrence of various defects in the machines or non-observance of the permitted or standard values in repair works causes the amount of vibration to increase and consequently the parts to be damaged and cause irreparable damage. In this paper, the rotor and simulation of the rotor of a turbofan engine used in industry are investigated. The characteristics of this type of rotor are high performance, lightness, and low amplitude of vibrations. Various parameters such as rotational inertia, gyroscopic torque, rotational loading, the effects of mass imbalance, and instability in modeling have been investigated. Natural frequencies, critical velocity, and calculations have been used by Ansys software. The results of the numerical analysis and simulation were compared and there was a good agreement between these two modes of investigations, indicating the validity and accuracy of simulation assumptions.